Polymer colour converter with very high modulation bandwidth for visible light communications - Vithanage, D; Kanibolotsky, A; Rajbhandari, S; Manousiadis, P; Sajjad, M; Chun, H; Faulkner, G; O'Brien, D; Skabara, P; Samuel, I; Turnbull, G (Royal Society of Chemistry, 2017)
For white light data communications, broad-band light emitting materials are required, whose emission can be rapidly modulated in intensity. We report the synthesis, photophysics and application of a novel semiconducting polymer for use as a high bandwidth colour converter, to replace commercial phosphors in white LEDs. The high modulation bandwidth (470 MHz) is 140 times higher than that measured using a conventional LED phosphor.